Heparin‐induced lipoprotein precipitation apheresis in dyslipidemic patients: A multiparametric assessment. Issue 3 (22nd February 2020) - Merolle, Lucia; Marraccini, Chiara; Latorrata, Alessia; Quartieri, Eleonora; Farioli, Daniela; Scarano, Luca; Fasano, Tommaso; Bergamini, Stefania; Bellei, Elisa; Monari, Emanuela; Tomasi, Aldo; Di Bartolomeo, Erminia; et al.
Abstract: Low‐density lipoprotein (LDL) apheresis (LA) selectively eliminates lipoproteins containing apolipoprotein B 100 (ApoB100) on patients affected by severe dyslipidemia. In addition to lowering lipids, LA is thought to exert pleiotropic effects altering a number of other compounds associated with atherosclerosis, such as pro‐ and anti‐inflammatory cytokines or pro‐thrombotic factors. More knowledge needs to be gathered on the effects of LA, and particularly on its ability to modify blood components other than lipids. We performed a multiparametric assessment of the inflammatory, metabolic and proteomic profile changes after Heparin‐induced lipoprotein precipitation (H.E.L.P.) apheresis on serum samples from nine dyslipidemic patients evaluating cholesterol and lipoproteins, plasma viscosity and density, metabolites, cytokines, PCSK9 levels and other proteins selectively removed after the treatment. Our results show that H.E.L.P. apheresis is effective in lowering lipoprotein and PCSK9 levels. Although not significantly, complement and inflammation‐related proteins are also affected, indicating a possible transient epiphenomenon induced by the extracorporeal procedure.